(untitled) (RT. A Journal on Research Policy and Evaluation, 2017)
This case study about the ethical behaviour in the field of scholarly publishing documents an exception on the rule for research articles in the medical journal BMJ Open that ICMJE disclosure forms of authors must be made available on request. The ICMJE, the International Committee of Medical Journal Editors, has developed these forms for the disclosure of conflicts of interest for authors of medical publications. The case refers to the form of the corresponding author of an article in BMJ Open on retraction notices (Moylan and Kowalczuk, 2016). The corresponding author is a member of the council of COPE, the Committee on Publication Ethics. I will argue that the unavailability of the form relates to personal conflicts of interest with the corresponding author about my efforts to retract a fatally flawed study on the breeding biology of the Basra Reed Warbler Acrocephalus griseldis. I describe my attempts to get the form and I will argue that its unavailability can be attributed to partial behaviour by BMJ, the publisher of BMJ Open. This study complements other sources reporting ethical issues at COPE.